1998
DOI: 10.1074/jbc.273.50.33135
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Major Bovine Brain Go α Isoforms

Abstract: G o is the major G protein in bovine brain, with at least three isoforms, G oA , G oB , and G oC . Whereas ␣ oA and ␣ oB arise from a single G o ␣ gene as alternatively spliced mRNAs, ␣ oA and ␣ oC are thought to differ by covalent modification. To test the hypothesis that ␣ oA and ␣ oC have different N-terminal lipid modifications, proteolytic fragments of ␣ o isoforms were immunoprecipitated with an N terminus-specific antibody and analyzed by matrix-assisted laser desorption ionization mass spectrometry. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 66 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…derived from posttranslational modifications of G␣ oA and G␣ oB , respectively (45). Within the nervous system, G␣ o activates neuronal Ca 2ϩ and K ϩ channels (46 -50).…”
Section: Discussionmentioning
confidence: 99%
“…derived from posttranslational modifications of G␣ oA and G␣ oB , respectively (45). Within the nervous system, G␣ o activates neuronal Ca 2ϩ and K ϩ channels (46 -50).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ciliopathies affecting the inner ear are often deaf and/or exhibit balance difficulties [ 22 ]. Patients with an affected olfactory epithelium often show a complete loss of smell (anosmia) [ 23 , 24 ], and patients with retinal ciliopathies often become blind (retinal degeneration) [ 25 , 26 , 27 ]. Impairment of more than one sensory organ results, for instance, in Bardet-Biedl [ 28 , 29 ] or Usher syndrome [ 30 , 31 ], two autosomal recessive genetic diseases ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ¢rst report of OPG structures is probably the description by McIntire et al [2], in 1942, of cyclic L,1-2 glucans found in culture ¢ltrates of a crown-gall organism (Agrobacterium tumefaciens). In this work, the glucans were essentially thought as a particular sub-class of exopolysaccharides.…”
Section: Introductionmentioning
confidence: 99%